The psychology of clothing : meaning of colors, body image and gender expression in fashion - Kodžoman, Duje (Array, 2019)
We select clothes that we’re purchasing and wearing according to the meaning we believe them to have, or the messages we believe them to send. But what are psychological consequences of clothing, and how does clothing express something about the user? To assess the state of knowledge about the communicative nature of fashion, the aim of this review was to provide a concise and succinct literature overview of over twenty empirical studies of the above-mentioned concept. The psychology behind clothing is classified into 3 thematic categories in this paper: a) the meaning of colors in clothing psychology; b) the socio-psycological impact of clothing; and c) gender (in)equality regarding clothing. Finally the last chapter brings a concise study of a few recent fashion shows, brands and trends. It is doubtless that both clothing and appearance serve as an important socializing influence and a form of communication.